Seminiferous epithelium damage after short period of busulphan treatment in adult rats and vitamin B12 efficacy in the recovery of spermatogonial germ cells - Vasiliausha, Sandi Regina [UNESP]; Beltrame, Flávia Luciana; de Santi, Fabiane; Cerri, Paulo Sérgio [UNESP]; Caneguim, Breno Henrique; Sasso-Cerri, Estela [UNESP] (Wiley, 2016)
Several different strategies have been adopted in attempt to recover from chemotherapy-damaged spermatogenesis that is often seen in oncologic patients. In this study, we have evaluated the impact of short period of exposure to busulphan on the haemogram and seminiferous epithelium of adult rats, focusing on spermatogonial depletion and Sertoli cell (SC) integrity. We then examined whether vitamin B12 supplementation improves the haematological parameters and spermatogonia number. The animals received 10 mg/kg of busulphan (BuG) or busulfan+vitamin B12 (Bu/B12G) on the first and fourth days of treatment. In H.E.-stained testicular sections, the areas of the seminiferous tubule (ST) and seminiferous epithelium were measured. The number of spermatogonia in H.E-stained and PCNA-immunolabelled testicular sections was quantified. The frequency of tubules with abnormal SC nuclei or TUNEL-positive SC was evaluated. Vimentin immunofluorescence in ST was also evaluated. In BuG and Bu/B12G, the animals showed leukopenia and thrombocytopenia, but the body weight reduced only in BuG. The areas of ST and seminiferous epithelium decreased in Bu/B12G and BuG. In BuG, the number of H.E.-stained and PCNA-immunolabelled spermatogonia reduced significantly. The frequency of tubules containing abnormal SC nuclei and TUNEL-positive SC increased and the vimentin immunoexpression pattern changed. In Bu/B12G, the number of H.E.-stained or PCNA-immunolabelled spermatogonia increased fourfold in comparison with BuG. The structural changes in ST after 6 days of busulphan exposure may be associated with the potential effect of this anti-neoplastic agent on SC. The increased number of spermatogonia in the busulphan-treated animals receiving vitamin B12 indicates that this vitamin can be an adjuvant therapy to improve the fertility in male cancer patients.
Keywords: apoptosis; chemotherapy; mitosis; Sertoli cell; spermatogenesis; vimentin